PEMIKIRAN REFLEKTIF DALAM PRAKTIK PROFESIONAL GURU IPAS DI SEKOLAH DASAR - Romi Kurniawan; Nova Riswanti; Dita Afianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reflective thinking is a crucial foundation of teacher professionalism, particularly in the context of integrated Science and Social Studies (IPAS) learning in elementary schools. However, its implementation continues to face structural and conceptual challenges, especially at the levels of policy and classroom practice. This study aims to systematically examine the concept, manifestations, as well as enabling and inhibiting factors of reflective thinking in the professional practice of IPAS teachers. Using a systematic literature review approach, data were analyzed through thematic analysis. The findings indicate that reflective thinking among IPAS teachers is not only oriented toward pedagogical improvement but also serves as an ethical means to realize the Pancasila Student Profile through the Merdeka Curriculum. Four main themes were identified: (1) conceptual foundations of reflection, (2) locally contextualized reflective practice, (3) structural barriers such as administrative burden, and (4) integration of character values into reflection. The results reveal a distinctive Indonesian discourse cluster that synthesizes global theoretical frameworks with local wisdom. This study recommends transforming teacher communities into collaborative reflective spaces and developing context-sensitive instruments to measure teacher reflectivity.